Els matisadors: connectors oracionals i textuals - Cuenca, Maria Josep (Caplletra. Revista Internacional de Filologia, 2015)
This paper is a contribution to the analysis of a group of connective items which caracteristically go with main connectives such as and, but, or... These connective expressions that we call MATISADORS have been included in the category of adverbials as conjunctive adverbs. We study their functioning in the sentence level and also in the text level.